2019
DOI: 10.1101/777102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mating-type specific ribosomal proteins control aspects of sexual reproduction inCryptococcus neoformans

Abstract: 29The MAT locus of Cryptococcus neoformans has a bipolar organization characterized by 30 an unusually large structure, spanning over 100 kb. MAT genes have been characterized by 31 functional genetics as being involved in sexual reproduction and virulence. However, classical 32 gene replacement failed to achieve mutants for five MAT genes (RPL22, RPO41, MYO2, PRT1, 33 RPL39), indicating that they are likely essential. In the present study, targeted gene replacement 34 was performed in a diploid strain f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Both the PR and HD mating‐type loci thus constitute ‘supergenes’ – loci transmitted as a single unit but composed of several genes (Schwander et al ., 2014). Some additional genes may have been incorporated into the mating‐type locus for proper nonself‐recognition; for example, in Cryptococcus neoformans it was shown that mating‐type specific alleles of ribosomal proteins were not interchangeable, being likely involved in promoting inheritance of nuclei of both mating types (Ianiri & Fang, 2020). Some basidiomycetes have multiple copies of the same pheromone alleles at their mating‐type locus, which need to be linked to each other and to the pheromone receptor gene for proper nonself‐recognition; such a situation, especially where duplication numbers differ between mating types (e.g.…”
Section: Gene Linkage At Mating‐type Loci In Fungi Ensures Proper Nonmentioning
confidence: 99%
“…Both the PR and HD mating‐type loci thus constitute ‘supergenes’ – loci transmitted as a single unit but composed of several genes (Schwander et al ., 2014). Some additional genes may have been incorporated into the mating‐type locus for proper nonself‐recognition; for example, in Cryptococcus neoformans it was shown that mating‐type specific alleles of ribosomal proteins were not interchangeable, being likely involved in promoting inheritance of nuclei of both mating types (Ianiri & Fang, 2020). Some basidiomycetes have multiple copies of the same pheromone alleles at their mating‐type locus, which need to be linked to each other and to the pheromone receptor gene for proper nonself‐recognition; such a situation, especially where duplication numbers differ between mating types (e.g.…”
Section: Gene Linkage At Mating‐type Loci In Fungi Ensures Proper Nonmentioning
confidence: 99%
“…Furthermore, the read depth on both DNA strands was analyzed with SAMtools and custom made perl scripts were used to calculate the read size distribution and 5'-nucleotide preference of the small RNA reads as previously described 87,88 .…”
Section: Crispr-mediated Genetic Complementation Of Znf3 Bt65mentioning
confidence: 99%
“…Normalization of the read counts to reads per million (RPM) was performed, allowing the comparison of the libraries. Furthermore, the read depth on both DNA strands was analyzed with SAMtools and custom made perl scripts were used to calculate the read size distribution and 5’-nucleotide preference of the small RNA reads as previously described 101, 102 .…”
Section: Methodsmentioning
confidence: 99%